Effectiveness of Open Educational Resources in Increasing Japanese Writing Skills - Agustine, Irawati; Permatasari, Kun Makhsusy; Robihim (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The purpose of this study was to obtain the effectiveness of the use of OER on Japanese writing skills. The research method uses a quantitative experimental approach with one pretest and posttest design. The design of this experimental method is quasi-experimental. The research was conducted in a writing class for the 2021-2022 academic year in the Japanese Language and Culture study program at a private university in Jakarta. The participants involved were students in a Japanese writing class of 50 students. So, the data is taken from observation and tests. The data analysis technique uses the t-test: Two-Pair Sample for the Mean. The results of the study concluded that t stat < t-table (-27.1284 < 2.0009). It can be said that Ho is rejected and H1 is accepted. It means that OER is effective for use in writing classes. It gave an impact on developing story ideas. The results of this study have implications for teachers that learning resources are varied and utilized through internet access.